Intervention to Improve Knowledge as an Effort to Prevent Sexual Violence among Adolescents - Mira Wahyu Kusumawati; Elok Faradisa; Amin Aji Budiman; Destiana Ayu Wardani (Community Service Journal : Jurnal Pengabdian Masyarakat Mardira, 2025)
Sexual violence among adolescents persists as a significant public health concern, particularly in rural areas with limited access to information. Insufficient adolescent knowledge regarding the definition, forms, and prevention of sexual violence increases the risk of victimization or perpetration. This community service program sought to enhance adolescents’ knowledge of sexual violence prevention through a structured health education intervention. Forty adolescent members of a karang taruna youth organization in Wonorejo Village participated in the program, which incorporated lectures, group discussions, and simulations. Knowledge acquisition was evaluated using pre-test and post-test questionnaires. Initial assessments indicated that most participants possessed low knowledge, with only 12.5% achieving a high level. Following the intervention, 62.5% of adolescents attained the high-knowledge category, and none remained in the low-knowledge category. These results indicate the effectiveness of community-based educational strategies in addressing information deficits at the village level. The findings align with existing literature that underscores the value of comprehensive sexual education in preventing sexual violence among adolescents. The intervention also fostered greater openness among adolescents in discussing sensitive topics and increased their willingness to report experiences or observations of violence. Sustainable implementation of this program is recommended, involving parents, teachers, and community leaders as agents of change. The outcomes of this initiative may serve as a pilot model for sexual violence prevention education in adolescent communities within similar contexts.